Redox-sensitive micelles composed of disulfide-linked Pluronic-linoleic acid for enhanced anticancer efficiency of brusatol - Zhang J (Dove Medical Press, 2018)
Jinming Zhang,1,* Xiaobin Fang,1,* Zeyong Li,2 Hon Fai Chan,3 Zhixiu Lin,4 Yitao Wang,1 Meiwan Chen1 1State Key Laboratory of Quality Research in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, Macau, China; 2Department of Laboratory Medicine, Guangdong No 2 Provincial People’s Hospital, Guangzhou, China; 3Department of Biomedical Engineering, Columbia University, New York, NY, USA; 4Faculty of Science, School of Chinese Medicine, Chinese University of Hong Kong, Shatin, Hong Kong, China *These authors contributed equally to this work Abstract: Brusatol (Bru) exhibits promising anticancer effects, with both proliferation inhibition and chemoresistance amelioration activity. However, the poor solubility and insufficient intracellular delivery of Bru greatly restrict its application. Herein, to simultaneously utilize the advantages of Pluronics as drug carriers and tumor microenvironment-responsive drug release profiles, a flexible amphiphilic copolymer with a polymer skeleton, that is, Pluronic® F68 grafting with linoleic acid moieties by redox-reducible disulfide bonds (F68-SS-LA), was synthesized. After characterization by 1H-nuclear magnetic resonance and Fourier transform infrared spectroscopy, the redox-sensitive F68-SS-LA micelles were self-assembled in a much lower critical micelle concentration than that of the unmodified F68 copolymer. Bru was loaded in micelles (Bru/SS-M) with high loading efficiency, narrow size distribution, and excellent storage stability. The redox-sensitive Bru/SS-M exhibited rapid particle dissociation and drug release in response to a redox environment. Based on the enhanced cellular internalization, Bru/SS-M achieved higher cytotoxicity in both Bel-7402 and MCF-7 cells compared with free Bru and nonreducible micelles. The improved anticancer effect was attributed to the remarkably decreased mitochondrial membrane potential and increased reactive oxygen species level as well as apoptotic rate. These results demonstrated that F68-SS-LA micelles possess great potential as an efficient delivery vehicle for Bru to promote its anticancer efficiency via an oxidation pathway. Keywords: poloxamer188, tumor micro-environment, glutathione, Brucea javanica, cancer treatment